The Impact of Open Data on Public Procurement - DUGUAY, RAPHAEL; RAUTER, THOMAS; SAMUELS, DELPHINE (Journal of Accounting Research, 2023)
ABSTRACT We examine how open procurement data affect the competitiveness of award procedures and the execution of government contracts. The European Union recently made its historical procurement notices available for bulk download in a cohesive and user‐friendly database. Comparing government contracts above and below EU procurement size thresholds, we find that, after the open data initiative, procurement officials are more likely to award treated contracts through open bidding. In cross‐sectional analyses, we document variation in the open bidding effect consistent with two underlying mechanisms: (1) increased scrutiny by NGOs and investigative journalists and (2) learning by national procurement regulators. However, treated contracts are also more likely to experience costly modifications because the shift to open bidding introduces rigidity that limits officials’ discretion in selecting suppliers based on private information. Overall, our evidence indicates that open procurement data promote competitive bidding but lead to contracts with weaker execution performance. These inferences also hold in an alternative open data setting.